Artificial Intelligence Applications in Engineering: A Case Study Analysis - Meghana Nuthalapati (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Artificial Intelligence (AI) is a revolutionary breakthrough in different industries such as engineering, where it can improve efficiencies, solve complex puzzles, or deliver innovation. This paper reviews various applications of AI in engineering, through case studies that show its real life implementation in various fields of engineering. A comprehensive analysis of some of the most critical AI technologies, including machine learning, neural networks, and natural language processing, is used in the paper to discuss what ways AI is transforming engineering design, predictive maintenance, quality control, and optimization. The case studies indicate that the actual benefits of AI implementation include cost savings, the enhanced decision-making process, and optimized performance. Balancing the various issues regarding AI integration like data quality, model transparency and ethical issues are also addressed. Finally, this paper offers insights on the ways the expansion of artificial intelligence in engineering is likely to go, which will necessitate further research and development in exploiting the benefits of AI in the future.